2011
DOI: 10.1371/journal.pone.0014622
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genomes Reveal Slow Rates of Molecular Evolution and the Timing of Speciation in Beavers (Castor), One of the Largest Rodent Species

Abstract: BackgroundBeavers are one of the largest and ecologically most distinct rodent species. Little is known about their evolution and even their closest phylogenetic relatives have not yet been identified with certainty. Similarly, little is known about the timing of divergence events within the genus Castor.Methodology/Principal FindingsWe sequenced complete mitochondrial genomes from both extant beaver species and used these sequences to place beavers in the phylogenetic tree of rodents and date their divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…The analysis of SINE distribution and the sequencing of mitochondrial genomes in rodents support the placement of Castor into the mouse-related clade (Horn et al 2011;Churakov et al 2010). Initial comparative painting investigations showed that the genome of C. fiber was extensively rearranged compared to squirrels (Graphodatsky et al 2008).…”
Section: Modified Comparative Map Of C Fibermentioning
confidence: 84%
“…The analysis of SINE distribution and the sequencing of mitochondrial genomes in rodents support the placement of Castor into the mouse-related clade (Horn et al 2011;Churakov et al 2010). Initial comparative painting investigations showed that the genome of C. fiber was extensively rearranged compared to squirrels (Graphodatsky et al 2008).…”
Section: Modified Comparative Map Of C Fibermentioning
confidence: 84%
“…These features corroborate our suggestion that Hystricomorpha is intermediate between Anomaluromorpha and Myomorpha+Castorimorpha. Although such an arrangement contradicts the latest data based on painting with human probes, sequencing of nuclear genes and the distribution of short interspersed elements all place Hystricomorpha in a basal position to the Anomaluromorpha+Myomorpha+ Castorimorpha clade (Ferguson-Smith and Trifonov, 2007;BlangaKanfi et al, 2009;Churakov et al, 2010;Horn et al, 2011). We therefore consider the fission of HSA 14/15 and the disruption of HSA 12 onto three fragments as convergent events that took place independently in hystricomorphs, myomorphs and castorimorphs.…”
Section: Overview Of Karyotype Evolution In Rodentsmentioning
confidence: 86%
“…The latest molecular data suggest, however, that these species should be considered a separate taxon independent from Sciuromorpha (Blanga- Kanfi et al, 2009;Horn et al, 2011). According to current taxonomy, Castorimorpha includes beavers, pocket and kangaroo mice, pocket gophers-some 102 species in all.…”
Section: Castorimorphamentioning
confidence: 99%
“…The long-range PCR strategy nevertheless remained an integral method for the majority of recent studies [e.g. (20,21)], especially to overcome many NGS platforms demand for moderate-to-high amounts of template DNA, which is of particular concern when dealing with limited material such as small invertebrates (22). However, optimizing long-range PCR can be tedious, in particular for previously uncharacterized organisms when the information required for primer design is scarce, whereas for difficult templates such as ancient DNA, long range PCR is no option at all, given the level of DNA degradation.…”
Section: Introductionmentioning
confidence: 99%